THE IMPORTANCE OF PATHOGENICITY FACTORS OF OPPORTUNISTIC MICROORGANISMS IN THE ASSESSMENT OF THEIR ROLE IN DISEASE DEVELOPMENT - E. S. Kunilova (Sankt-Peterburg : NIIÈM imeni Pastera, 2014)
Absract. The following pathogenicity factors of microorganisms prevailed in case of acute inflammation of the upper respiratory tract were studied: adhesive characteristics, hemolytic, hemagglutination, neuraminidase activities. It was established that microorganisms of the Moraxella genius have strongest adhesive characteristic. The high hemolytic and hemagglutination activity is inherent in microorganisms of the Staphylococcus and Streptococcus genius. In the case of isolation from patients microbial associations the clinical symptoms and pathogenicity factors of microbes-associates were more apparent.